GAMBARAN KADAR ASAM URAT, GLUKOSA DARAH DAN TINGKAT PENGETAHUAN LANSIA DI DESA SAMSAM KECAMATAN KERAMBITAN KABUPATEN TABANAN - ida arjani (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2018)
Background Uric acid is an adjunct product of normal metabolism of the digestion of protein foods containing purines or from the decomposition of purines (damaged body cells), which should be excreted through the kidneys, feces or sweat. While blood glucose levels should be maintained in sufficient concentration to provide nutrients for the organs of the body. Conversely, too high glucose concentrations can also have negative effects such as osmotic diuresis and cell dehydration.The purpose of this study was to determine the description of uric acid levels, blood glucose and level of knowledge of the elderly in Samsam Village, Kerambitan District, Tabanan Regency.Method, The type of research used is descriptive. The population in this study were all elderly in Samsam village area with sample size of 57 samples. Sampling technique used Nonprobability Sampling and sampling with Accidental Sampling.Result.From 57 respondents, there were 14 men (25%), women 43 people (75%), age group ≤ 60 years were 18 persons (32%) and age group 60 years were 39 people (68% ). The results of examination of uric acid levels of respondents in the normal category of 7 people (12%) and high 50 people (88%). Blood Glucose Levels when the respondents were normal 52 people (91%) and high 5 people (9%). Knowledge of respondents was 22 people (39%) in good category and 35 people (61%) in medium category.Conclusion, as many as 88% of respondents have high uric acid levels, 9% of respondents have high blood glucose levels and 61% of respondents have knowledge in the category of being Keywords: Uric Acid Level, Blood Glucose, Elderly’s knowledge